Isachsen decca chain, southern sheet / the geographical grid and topographical features were drawn by the Canadian Hydrographic Service from the latest information supplied by the Surveys and Mapping Branch to December 1960 - Canada. Department of Mines and Technical Surveys (Ottawa : Dept. of Mines and Technical Surveys, 1960)
Color; 1:495,000